Eclipse of God in Scientific Discourse: A Study of Secular Epistemology - Adhikari, Bhoj Raj (Pancasila International Journal of Applied Social Science, 2025)
This study examines the dominant faith in God among major religious communities—Hinduism, Buddhism, Christianity, and Islam—and explores how scientific inquiry challenges this faith across diverse cultural contexts. It explores the evolution of belief systems from historical origins to the present transitional phase characterized by the rise of secular epistemology. The research further examines the conflicting perspectives between theist and atheist groups, assessing the extent to which these worldviews have shaped societal norms and individual livelihoods. Ultimately, the study concludes by contrasting theological conceptions of God with empirical, fact-based understandings, highlighting the implications of this epistemological shift on contemporary society.